Ultrasound Elastographic Findings of Mammary Fibromatosis - Ping He; Li-Gang Cui; Yu-Tao Lei; Jian-Ying Liu; Jin-Rui Wang (Case Reports in Radiology, 2015)
Mammary fibromatosis is an uncommon, benign tumor of the breast. It is locally aggressive and has a high rate of recurrence. Its clinical presentation and imaging results always call for suspicion of malignancy. Here we describe a case of mammary fibromatosis with clinical manifestation, radiographic and pathologic results, and imaging findings from ultrasound elastography.